2011
DOI: 10.3201/eid1703.100882
|View full text |Cite
|
Sign up to set email alerts
|

Q Fever in France, 1985–2009

Abstract: To assess Q fever in France, we analyzed data for 1985–2009 from the French National Reference Center. A total of 179,794 serum samples were analyzed; 3,723 patients (one third female patients) had acute Q fever. Yearly distribution of acute Q fever showed a continuous increase. Periodic variations were observed in monthly distribution during January 2000–December 2009; cases peaked during April–September. Q fever was diagnosed more often in patients in southeastern France, where our laboratory is situated, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
102
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 102 publications
(112 citation statements)
references
References 22 publications
5
102
0
5
Order By: Relevance
“…In a previous study, Frankel and others showed that an increase in the level of phase I IgG is correlated with higher PPVs for the diagnosis of endocarditis in France. 28 The PPVs for possible or definite endocarditis increase with the levels of IgGI titer, and we found comparable results in this study for patients from the Marseille area. For patients from the Cayenne area, we could not use the same serological cut-off that is used to diagnose cardiovascular infections in French patients 7 because the PPV of phase I IgG for patients from this area is much lower.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In a previous study, Frankel and others showed that an increase in the level of phase I IgG is correlated with higher PPVs for the diagnosis of endocarditis in France. 28 The PPVs for possible or definite endocarditis increase with the levels of IgGI titer, and we found comparable results in this study for patients from the Marseille area. For patients from the Cayenne area, we could not use the same serological cut-off that is used to diagnose cardiovascular infections in French patients 7 because the PPV of phase I IgG for patients from this area is much lower.…”
Section: Discussionsupporting
confidence: 84%
“…1,8,21 In large studies in Switzerland 27 and the Netherlands, 8 half of the patients with acute infections were asymptomatic, and only 5-20% of acute infections were severe enough to prompt a diagnostic test. 1,7 In the Marseille area, the annual reported incidence of diagnosed acute Q fever was 1.9 cases/100,000, 28 which is 25-fold less than the annual estimated incidence of Q fever, which is 50 cases/100,000. 2 No annual estimated incidence is available for the Cayenne area, but the incidence of diagnosed acute Q fever in Guiana, which was 37 cases/ 100,000 in 1996 and increased to 150 cases/100,000 in 2005, 14 is most likely underestimated, despite the severity of the disease.…”
Section: Discussionmentioning
confidence: 94%
“…4 Levels within the range of 800-1024 have been mostly accepted. 4,9 However, Frankel et al 10 have demonstrated that the positive predictive value of phase I IgG = 800 for proven chronic infection was only 37%. In children, the immune response after acute infection is very high, and titers up to 3200 have been demonstrated without chronic infection.…”
Section: Discussionmentioning
confidence: 99%
“…Les réponses immunitaires à C. burnetii MST 17 sont marquées par des titres d'anticorps IgG de phase I très élevés . Un titre élevé d'IgG de phase I persistant plusieurs mois après les symptômes est reconnu comme étant associé aux formes chroniques de la maladie mais la valeur prédictive positive d'endocardite pour des IgG de phase I >800 est faible en Guyane (Frankel et al 2011;. Cette virulence spécifique de C. burnetii MST 17 pourrait être liée à une délétion d'un fragment de 6105 pb qui correspond à la région de l'opéron hlyCABD du système de sécrétion type I (T1SS) (D'Amato et al 2015).…”
Section: Caractéristiques Cliniques Et Microbiologiquesunclassified